HUBUNGAN JARAK KANDANG DAN PENGOLAHAN LIMBAH TERNAK BABI SERTA KEPADATAN LALAT DALAM RUMAH DENGAN KEJADIAN DIARE PADA BALITA DI DESA SABULAN KECAMATAN SITIOTIO KABUPATEN SAMOSIR TAHUN 2013 - Wati Sitohang; wirsal hasan; Devi Nuraini Santi (Lingkungan dan Kesehatan Kerja, 2013)
The correlation between the distance corral and the pigs waste processing and density of flies in the house with diarrhea dissease in toddlers in Sabulan Village Sitio-tio distric Samosir regency in 2013. Diarrhea disease is a major cause of high morbidity and mortality in humans, especially in young infants and toddlers. Globally, diarrhea causes 16% mortality, whereas in Indonesia, diarrhea is a major cause of death in young children, which is 25.2%. Diarrhea disease is generally influenced by the characteristics of the community and environmental health. One of the environment role in causing disease is as reservoir of agent with or without vector.This study used cross-sectional design with the sample was the entire population, which is 75 people. The inclusion criteria of the sample were those who have have toddler (1-4 years) and raise pigs. The data were analyzed using univariate analysis and Chi Square test as bivariare analysis. This study aimed to know the relationship between the distance of corral and the pigs waste treatment and the density of flies in the house with the incidence of diarrhea in toddlers. Results of research based on bivariate analysis with a rate of 95%, statistical test results obtained for corral distance is ρ = 0179 (ρ> 0.05), the pigs waste processing is ρ = 0.492 (ρ> 0.05) and density flies in the house is ρ = 0.567 (ρ> 0.05).Based on research results, it was concluded that there was no correlation between the distance corral and the pigs waste processing as well as density of flies in the house with the incidence of diarrhea in toddlers. Keywords: diarrhea, toddler, pigs, flies density